Abnormal venous return: Still a challenge for electrophysiology procedures? A case report. Issue 5 (May 2021) - Robles, Antonio Gianluca; Borrelli, Alessio; de Ruvo, Ermenegildo; Sciarra, Luigi; Scarà, Antonio; De Luca, Lucia; Grieco, Domenico; Calò, Leonardo
Abstract: Catheter ablation of cardiac arrhythmias is usually performed through the femoral venous approach. Systemic venous return anomalies such as interruption of the inferior vena cava may represent a challenge during electrophysiological procedures. A 55-year-old patient with previous surgical correction of abnormal pulmonary venous return was admitted for poorly tolerated atrial flutter recurrences. He also had an interrupted inferior vena cava continuing as azygos vein and left superior vena cava draining via coronary sinus into the right atrium. Cavotricuspid isthmus radiofrequency ablation was successfully performed through the persistent left superior vena cava using a three-dimensional (3D) electroanatomical mapping system. Despite systemic venous abnormalities may potentially have important implications during electrophysiological procedures, arrhythmias can be successfully ablated with the aid of 3D electroanatomical mapping systems. <Learning objective: Congenital venous return anomalies can represent significant difficulties in accessing catheters to the cardiac chambers during electrophysiological procedures, which may be facilitated by three-dimensional mapping systems. Radiofrequency ablation of the cavotricuspid isthmus can be successfully performed using the femoral approach and introducing catheters into the right atrium sequentially through the femoral-iliac venous axis, the azygos vein, the persistent left superior vena cava, and the coronary sinus.>